Colorectal cancer statistics, 2014 - Siegel, Rebecca; DeSantis, Carol; Jemal, Ahmedin (CA: a cancer journal for clinicians, 2014)
Colorectal cancer is the third most common cancer and the third leading cause of cancer death in men and women in the United States. This article provides an overview of colorectal cancer statistics, including the most current data on incidence, survival, and mortality rates and trends. Incidence data were provided by the National Cancer Institute's Surveillance, Epidemiology, and End Results program and the North American Association of Central Cancer Registries. Mortality data were provided by the National Center for Health Statistics. In 2014, an estimated 71,830 men and 65,000 women will be diagnosed with colorectal cancer and 26,270 men and 24,040 women will die of the disease. Greater than one‐third of all deaths (29% in men and 43% in women) will occur in individuals aged 80 years and older. There is substantial variation in tumor location by age. For example, 26% of colorectal cancers in women aged younger than 50 years occur in the proximal colon, compared with 56% of cases in women aged 80 years and older. Incidence and death rates are highest in blacks and lowest in Asians/Pacific Islanders; among males during 2006 through 2010, death rates in blacks (29.4 per 100,000 population) were more than double those in Asians/Pacific Islanders (13.1) and 50% higher than those in non‐Hispanic whites (19.2). Overall, incidence rates decreased by approximately 3% per year during the past decade (2001–2010). Notably, the largest drops occurred in adults aged 65 and older. For instance, rates for tumors located in the distal colon decreased by more than 5% per year. In contrast, rates increased during this time period among adults younger than 50 years. Colorectal cancer death rates declined by approximately 2% per year during the 1990s and by approximately 3% per year during the past decade. Progress in reducing colorectal cancer death rates can be accelerated by improving access to and use of screening and standard treatment in all populations. CA Cancer J Clin 2014;64:104–117. © 2014 American Cancer Society.